Sankofa (Haile Gerima, 1993) : la mémoire de l’esclavage dans la conscience diasporique - Delphine Letort (Transatlantica)
Sankofa is the eighth film made by Ethiopian director Haile Gerima, who has been living in exile in the United States since 1967. Based on an original script, written by the filmmaker himself, Sankofa is a slave narrative which, however, has no historical value since it was developed through creative writing. Gerima pays little attention to historical details as he retraces the time journey of a young African-American woman, Mona, into the past of slavery during a visit of Cape Coast Castle. Between present-day Ghana and the American plantation of the past, the filmmaker overcomes the time and space gap to develop diasporic consciousness. Sankofa promotes an Afrocentric discourse on the memory of slavery, which we will examine through a detailed study of its representation of the past and of the construction of the female black body on screen.